2016
DOI: 10.1111/xen.12247
|View full text |Cite
|
Sign up to set email alerts
|

Jewish ethics and xenotransplantation

Abstract: Background Although exclusively secular approaches to xenotransplantation are methodologically necessary to establish a fundamental verdict on its theoretical ethical acceptability, it is nevertheless pragmatically appropriate to take into account specifically religious positions, as religion is a factor relevant to societal acceptability. Apart from the aspect of societal acceptability, Jewish bioethics, like other religiously embedded ethics, may enrich the broader ethical discourse on xenotransplantation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 25 publications
(39 reference statements)
0
16
1
1
Order By: Relevance
“…In the three major monotheistic religions, it is part of their established practice to take care of the sick . In the 20th century, special pastoral care has been developed in hospitals in German‐speaking countries.…”
Section: Exploring the “Pastoral Challenges Of Xenotransplantation”—amentioning
confidence: 99%
“…In the three major monotheistic religions, it is part of their established practice to take care of the sick . In the 20th century, special pastoral care has been developed in hospitals in German‐speaking countries.…”
Section: Exploring the “Pastoral Challenges Of Xenotransplantation”—amentioning
confidence: 99%
“…[3][4][5][6][7] Public opinion surveys have found that, in general, the perception of and willingness to consider XTx are favourable [8][9][10][11][12] , although the influence of religious beliefs was less straightforward. 8,[10][11][12] While theological discussions have suggested no specific prohibition from Abrahamic theological traditions (ie Jewish, Christian, and Muslim), [3][4][5][6][7] a review of public opinion survey responses related to the role of religious beliefs in the decision to consider a XTx was more complex. 8,[10][11][12] One recent study suggested that it was the amount of detailed information and procedure results that would have the greatest influence on religious acceptance of the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…The theological‐ethical perspectives and the complex issues that XTx raises for society and the potential recipient have been widely reported . Public opinion surveys have found that, in general, the perception of and willingness to consider XTx are favourable, although the influence of religious beliefs was less straightforward .…”
Section: Introductionmentioning
confidence: 99%
“…As initial clinical trials draw closer, ethics [79], acceptance of xenotransplantation by hospital personnel [80], and by the general population with different cultural and religious backgrounds [8183], are topics of importance. Schuurman has recently comprehensively reviewed regulatory aspects of xenotransplantation in Europe and in the United States in his seminal papers [8485].…”
Section: Introductionmentioning
confidence: 99%